2019
DOI: 10.1002/ps.5330
|View full text |Cite
|
Sign up to set email alerts
|

Triazolide strigolactone mimics as potent selective germinators of parasitic plant Phelipanche ramosa

Abstract: BACKGROUND: Strigolactones are a unique class of plant metabolites which serve as a rhizosphere signal for parasitic plants and evocate their seed germination. The expansion of these parasitic weeds in the food crop fields urgently calls for their increased control and depletion. Simple strigolactone analogues able to stimulate seed germination of these parasitic plants may represent an efficient control measure through the induction of suicidal germination. RESULTS: Triazolide-type strigolactone mimics were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Indeed, we showed that parasitic seeds of genetic group 1 were highly sensitive to strigolactone synthetic enantiomers as they were able to germinate with up to 10 -12 M of (+)-GR24 and (-)-2’- epi -GR24. This was consistent with previous work that showed that P. ramosa seeds from oilseed rape plots were ten to hundred times more sensitive to (±)-GR24 and to different conformations of GR24 than seeds from hemp plots ( Boyer et al., 2014 ; Dvorakova et al., 2018 ; Dvorakova et al., 2019 )⁠. Also, seeds from oilseed rape and hemp plots perceived at a lower concentration the (+)-GR24 and (-)-2’- epi -GR24, and were less sensitive to GR24 with non-natural conformation ( de Saint Germain et al., 2019 )⁠.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, we showed that parasitic seeds of genetic group 1 were highly sensitive to strigolactone synthetic enantiomers as they were able to germinate with up to 10 -12 M of (+)-GR24 and (-)-2’- epi -GR24. This was consistent with previous work that showed that P. ramosa seeds from oilseed rape plots were ten to hundred times more sensitive to (±)-GR24 and to different conformations of GR24 than seeds from hemp plots ( Boyer et al., 2014 ; Dvorakova et al., 2018 ; Dvorakova et al., 2019 )⁠. Also, seeds from oilseed rape and hemp plots perceived at a lower concentration the (+)-GR24 and (-)-2’- epi -GR24, and were less sensitive to GR24 with non-natural conformation ( de Saint Germain et al., 2019 )⁠.…”
Section: Discussionsupporting
confidence: 93%
“…Analogues of strigolactone have been synthesized, such as GR24 and Nijmegen 1, which can effectively induce the germination of broomrape seeds (Wigchert et al 1999 ). However, their poor stability in soil and the high cost of producing these compounds limit their use in agricultural production (Babiker et al 1987 ; Dvorakova et al 2019 ) synthesized simple and stable strigolactone mimics with selective activity against Phelipanche ramosa . Kuruma et al ( 2021 ) discovered a structurally hybrid compound that can induce spontaneous germination and inhibit subsequent radical growth.…”
Section: Introductionmentioning
confidence: 99%
“…Because the requisite temperature for seed germination of the broomrapes is normally not higher than that of Striga spp. seeds, the broomrapes can survive in the most subtropical and temperate zones including Asia, Australia, Mediterranean, and eastern Europe, besides Africa. , As far as we know, there are 11 species of Orobanche distributed in China, and O. cumana and O.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is still impractical in the developing countries considering the high expense of this methodology. Moreover, this method was also shown to be less effective to some types of the broomrapes …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation